The Effect of the Inflation Rate and Human Development Index on the Open Unemployment Rate in Cirebon City in 2013-2022 - Fitriyani Tiarawati; Syaeful Bakhri; Wasman Wasman (Cirebon International Journal of Economics and Business, 2024)
The problem of unemployment is still the main problem in an economy in various regions, including Cirebon City. Unemployment occurs due to an imbalance between the number of available job opportunities. This study aims to find out how the Inflation Rate, Human Development Index (HDI) affect the Open Unemployment Rate in Cirebon City in 2013-2022. The motto used in this study is a quantitative method with the data source used for this study being secondary data obtained from the Central Statistics Agency (BPS). The data analysis technique used is multiple linear analysis.The results of the study show that from the results of the research data, it can be interpreted that the results of the partial test (t-test) show that the variable of the inflation rate obtained a calculated value greater than the ttable, which is -13,347 > 2,178 with a significant value of 0.00 < 0.05, then it can be interpreted that the variable of the inflation ratehave a negative and significant influence on the variable of the open unemployment rate. The human development index variable obtained a tcount value greater than the ttable, which is 10,937 > 2,178 with a significant value of 0.00 < 0.05, it can be interpreted that the human development index variable has a positive and significant influence on the variable of the open unemployment rate. The results of the simultaneous test (test f) showed that the variable of the inflation rate and the variable of the human development index obtained a value of Fcal greater than that of the Ftable, which was 89,091 > 3.89 with a significant value of 0.00 > 0.05, so it can be stated that the variables of the Inflation Rate and the Open Unemployment Index have a significant effect on the Open Unemployment Rate in Cirebon City in 2013-2022.